DOI: 10.14264/uql.2018.177
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in very preterm infants during their hospital stay

Abstract: Background The survival of preterm infants has increased over the past decades. However, these infants are still at high risk of poor growth especially those born at <32weeks gestation (very preterm infants, VPT infants). The American Academy of Paediatrics recommends that the "postnatal growth of preterm infants in both their anthropometric indices and body composition should be the same as the normal fetus of the same gestational age". VPT infants at term equivalent age have been reported to have an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…It has thus been suggested that any obesity association may be more of a risk in older gestational age preterm infants with no co-morbidities than in those of earlier gestational age (39) . More recently, researchers have identified that preterm infants have altered body composition, characterised predominantly by less fat-free mass but a maintained fat mass, leading to a greater percentage total body fat (13,40,41) . Further research into the childhood and later-life obesity risks of timing of the introduction of solid foods is required in these at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…It has thus been suggested that any obesity association may be more of a risk in older gestational age preterm infants with no co-morbidities than in those of earlier gestational age (39) . More recently, researchers have identified that preterm infants have altered body composition, characterised predominantly by less fat-free mass but a maintained fat mass, leading to a greater percentage total body fat (13,40,41) . Further research into the childhood and later-life obesity risks of timing of the introduction of solid foods is required in these at-risk populations.…”
Section: Discussionmentioning
confidence: 99%